A survey of some aspects of birthday celebration - Rojaka, Darja; Lesinskienė, Sigita (Acta medica Lituanica, 2018)
Background. The tradition of celebrating the day of birth of an individual is thought to have existed since the ancient times. Depending on the culture, religious beliefs, and the geographic location, occasions for ritual performance differ greatly. The aim of this pilot study was to investigate how students in Lithuania evaluate the importance of their birthday. Materials and methods. An “Invitation to Remember Your Birthday” questionnaire was created by the authors to collect the responses for evaluation. The questionnaire consisted of 15 questions divided into four parts. It assessed how and what the respondents felt on their annual birthday, about the organization of the celebration, gift-receiving, and the value of the ritual. Results. A total of 309 medical students of Vilnius University completed the survey (n = 146 year 4, n = 163 year 5). The results suggested that the birthday is an important individual occasion, which students tend to celebrate annually. The respondents tend to feel better and more loved on the day of their birthday. Conclusions. Birthday is seen as an opportunity to spend time with friends and family, have a break from daily responsibilities, and receive attention from people around them. Birthday celebration of medical students is affected by their social and cultural context. The findings of this study may be relevant for future studies when searching for ageand culture-appropriate ways to use birthday celebration as possible means of improving mental health. The current data can be used for longitudinal and cross-cultural comparisons.